UTILIZING THE OPPORTUNITIES OF BUSINESS INCUBATORS IN THE DEVELOPMENT OF INDUSTRIAL ENTERPRISES - Narzullaev Shodiyor Eshpulatovich (Scholar Express Journals, 2023)
In this article, the effective use of opportunities of business incubators in the development of metallurgical industry enterprises is discussed. In particular, the economic advantages of the creation of new workplaces as a result of supporting and implementing the results of innovative scientific and technological development projects of scientists contributing to the activity of industrial enterprises are highlighted.
Keywords: industry; metallurgy; import; cost